In Silico Structure-based Screening of Potential Anticancer Bioactive Natural Constituents from African Natural Products - Kraim, Khairedine; Boudjedir, Atidel; Saihi, Youcef; Chikh, Fatima Zohra Oueld; Slatnia, Yassira; Ferkous, Fouad (Letters in Drug Design & Discovery, 2024)
IntroductionInhibitors of topoisomerases, essential regulators of cancer development, are promising as cancer treatments. These enzymes regulate DNA topology and eliminate topological constraints during various biological processes, including replication, transcription, and recombination. Nature has continually offered scientists pathways to explore the development of new drugs. Indeed, since ancient times, various plant extracts have been utilized in treating multiple pathologies.ObjectiveIt’s intriguing to diversify the therapeutic classes of natural topoisomerase 1 inhibitors. We aimed to explore the relationship between the toxicity of certain medicinal plants in North Africa and their anti-topoisomerase 1 enzyme activity. This investigation aims to discover potentially valuable compounds for fighting cancer by inhibiting the Topo1 enzyme, enriching the anticancer therapeutic class.MethodsThis study has conducted a virtual screening of the African Natural Products Database to identify new scaffolds as topoisomerase 1 inhibitors. Molecular docking as a structure-based drug design approach was selected as one of the best approaches, and the complex code ID: 1K4T was used for this purpose.Results and DiscussionThe molecular docking of more than 5790 natural products extracted from this database was docked into the binding site of the above-cited complex using the Modlock optimizer and Moldock score as search and scoring function algorithms, respectively. The top-ranked compounds have been assessed, analyzed, and compared to Topotecan and Irinotecan as reference ligands and drugs.ConclusionConsequently, the seven natural products have shown a strong affinity to topoisomerase 1 and DNA. They establish a clear link between topoisomerase 1 inhibition and the anticancer activity of their corresponding plant extracts. Therefore, these hits are promising and serve as a base for further development of new topoisomerase 1 inhibitors.
Keywords: Natural products